Scientific and applied components of a multicriteria system for assessing the innovative development of enterprises: imperatives of interaction between integrated structures - Onikienko, N.; Petrukha, N.; Ryzhakova, G. (Ways to Improve Construction Efficiency, 2023)
In the modern context of globalization and rapid development of information technologies, localized production networks and regionally-functional business clusters are gaining increasing importance. These forms of economic organization allow enterprises to achieve high levels of efficiency and competitiveness through interaction, cooperation, and knowledge exchange among participants. The functioning of enterprises within such structures fosters innovation, optimization of production processes, cost reduction, and improved adaptability to changes in the market environment. The article examines models of enterprise functioning within localized production networks–intersectoral business clusters in the format of an agro-construction cluster. Clusters are presented as an implementation of a new model of innovative development for enterprises, which significantly enhances their performance through territorial concentration and cooperation. Theoretical and methodological prerequisites of models of cyclic territorial and chronological economic dynamics are analyzed, revealing the relationship between economic functionalities, as well as models for assessing and forecasting changes in the internal environment of enterprises within the cluster. Clusters, particularly the creation of an agro-construction cluster, are considered an effective organizational model that ensures synergy between agricultural and construction enterprises through the shared use of resources and innovative solutions. Economic and mathematical models are proposed to help determine the innovative development of enterprises: a model for optimizing the synergistic effect (linear programming, a regression analysis model for forecasting the synergistic effect, a multi-agent cluster modeling model, a network interaction model of companies within a cluster, evaluation, and forecasting changes in the internal environment of structural units (at the enterprise level), a dynamic programming model for long-term planning, and a model for evaluating and forecasting changes in the internal environment of structural units (at the enterprise level). Special attention is given to integrated enterprises within a territorial-production cluster using the example of the agro-construction cluster of PJSC "MHP," which contributes to expanding opportunities for innovative development through the implementation of new technologies and management practices.